The Influence Of Income And Interest Rate On Pattern Of Community Investment In Central Kalimantan - Aceng Mantano; Washington Siagian (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2018)
ABSTRACT The aims of study is to find out how the influence of income and interest rates on investment patterns of people in Central Kalimantan. The method of data collection is done by library studying of secondary data related to the parameters of studied. The analytical tool used is multiple regression analysis method. The results showed that: a) Investment by PMDN Central Kalimantan is partially influenced by Income Perkapita Society and Interest Rate Savings. This is indicated by statistical test results (partial test) that is significant at the level of confidence of 95% or (?) = 0.05 where t-arithmetic XI (Revenue per capita) of 2.016> t-table = 1.860 and t-count X2 (Interest Rate of Savings) = 2,172> t-table = 1,860. b) Statistical test results F (Test in General). Per Capita Revenue and Interest Rate Savings have significant effect on investment, especially PMDN of Central Kalimantan province.